(untitled) (Journal of Global Accounting, 2024)
The study examined impact of independent director educational background and tenure on financial performance of listed financial companies in Nigeria from 2015-2023. The study was guided by two research questions and two hypotheses were formulated and tested in the study. The study was anchored on resource dependency theory while the ex post facto research design was applied in this study. The population of this study is forty-nine (49) financial companies listed on the floor of the Nigerian Exchange Group (NGX) for the period between 2015 and 2022. The study population figure was gotten from the Nigerian Exchange Group Website 2022. The population of the study comprised of listed banks and insurance companies. The study’s final sample size was determined using a strategy of purposeful non-probability sampling. Therefore, a total of thirty-seven (37) quoted financial companies comprised of deposit money banks and insurance companies on the Nigerian Exchange Group (NGX) formed the sample size of this study. The study relied on only secondary data, with the major source being the annual financial statements of the sampled companies for a period of eight (8) years (2015 to 2022). This study employed the use of the Panel Least Square (PLS) analysis technique. The study revealed that independent director’s educational background has significant effect on corporate performance (ROA) of listed financial companies in Nigeria for the period under investigation and that independent director tenure has no significant effect on corporate performance of listed financial companies in Nigeria for the period under investigation. Based on the findings, it was recommended among others that the management of financial companies in Nigeria should consider the appointment of independent directors of their respective institutions on based on the financial expertise of the individual so as to enhance corporate performance of listed financial companies in Nigeria.